# How do you factor #3a^2 - 8b + 12a -2ab#?

##### 1 Answer

#### Answer:

#### Explanation:

First swap the second and fourth terms, then factor by grouping:

#3a^2-8b+12a-2ab#

#=3a^2-2ab+12a-8b#

#=(3a^2-2ab)+(12a-8b)#

#=a(3a-2b)+4(3a-2b)#

#=(a+4)(3a-2b)#

Why did I think to swap the second and fourth terms first?

The original expression contains a mixture of terms of degree

By putting the terms of degree

Having noted the ratio of

By this careful choice, the rest of the factoring went smoothly.